Genetic polymorphisms influencing the response of antidepressants - Serretti, Alessandro (Henry Stewart Talks, 2007)
Pharmacogenetic studies in mood disorder, Candidate genes as possible genetic predictors of antidepressant response efficacy, Serotonin transporter gene (5-HTTLPR), Serotonin receptor 1A (5HT1A-C-1019G), G-protein beta3-subunit (Gbeta3-C825T), Serotonin receptor 2A (5HT2A, 102TC), Tryptophan hydroxylase gene (TPH-A218C), Associations for FKBP5 and other unreplicated gene variants, Follow up pharmacogenetic studies, Circadian Locomotor Output Cycles Kaput (CLOCK-T3111C) gene variants are associated with insomnia and other features, PER 15 variants and mood disorder phenotypes, Neural networks: the example of 5-HTTLPR and TPH polymorphisms
Updated at 2012/12/01